PSYCHOLOGIC ANALYSES OF THE NOTION OF ASYMMETRY IN THE PROCESS OF COMMUNICATION (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article the psychologic changes in the process of speech are discussed. The influence of psychologic and affect states in the process of speech is analyzed on the bases of the texts taken from fiction.